Relationship between perceived social support and depression in convicts using substance - Aslan, Aylin; Arıcak, Osman Tolga; Karadaşlı, Bilge (Journal of Dependence, 2019)
Objective: The aim of this study is to examine the relationship between perceived social support and depression in convicts using substance.Method: The study sample consisted of a total of 176 persons, including 86 persons who were convicted and using substance in probation unit and 90 persons who were randomly selected by the researchers. Sociodemographic information of the participants was collected and Multidimensional Perceived Social Support Scale (MSPSS) and Beck Depression Inventory (BDI) were all administered.Results: Study results revealed that there was a significant moderate and negative relationship between BDI and total MSPSS and Significant Other subscale mean scores. However, a negative and poorly significant relationship was found between BDI and Family and Peer subscale mean scores. MSPSS mean scores were found to be higher in individuals who were not using substance and were not convicted and BDI mean scores were found to be higher in convicts using substance.Conclusion: Psycho-social programs aiming to develop social support for convicts using substance will have a positive effect on the level of depression.
Keywords: Substance; social support; depression